Urban Reality Construction of BPJS Services: Comparative Study at Mangusada Hospital and Clinic - Damayanti, Ni Made Ayu Nindya; Mudzakkir, Moh; Hanindraputri, Eufrasia Kartika; Sadewo, Fransiscus Xaverius Sri; Adawiah, Wardatul (Universitas Sebelas Maret, 2026)
This study analyzes how urban communities construct social reality regarding BPJS Health services through direct experiences in two different healthcare institutions, namely RSUD Mangusada and Mengwi I Clinic, Badung Regency. The research is grounded in the dynamics of urban society characterized by high mobility, social diversity, and strong expectations for public services that are fast, efficient, and humane. A qualitative approach with a comparative design was employed to explore the perceptions of patients, health workers, and institutional managers. Data were collected through in-depth interviews, participatory observations, and documentation. The findings reveal differences in social constructions between the two institutions. RSUD Mangusada is often perceived as slow, bureaucratic, and less communicative, particularly in relation to long queues, extended waiting times for medication, and complaint mechanisms that lack transparency. In contrast, Mengwi I Clinic is considered more efficient, friendly, and closer to the community, with orderly queues, open communication, and services that adapt to local needs. Factors such as staff attitudes, transparency of information, accessibility, and the alignment of facilities with patient expectations play a crucial role in shaping public perceptions. Balinese cultural values that emphasize politeness and harmony further strengthen the meaning of health services, making social interaction an essential element in building trust toward healthcare institutions. These findings affirm that perceptions of BPJS services are not merely the result of formal structures but are socially constructed through collective experiences and repeated interactions.